Perception of public on Covid-19 immunisation program in Malaysia - Nurhafizah Yusoff; Muhammad Ridhwan Sarifin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Due to the COVID-19 pandemic, many countries have implemented the vaccination program to combat the spread of virus in order to return to a normal life after the quarantine period. The success of vaccination has shown the decrease in infection and death besides the practice of physical distancing. This article will discuss the category of people who have doubt, confidence and their view towards The National COVID-19 Immunisation Programme (NIP) in Malaysia. A quantitative survey was made through an online survey using Google Form. The recruitment of the survey participants was based on a convenience sampling method. This survey was conducted on Malaysian citizens of age from 18 to 57 years old and analysed using One-way ANOVA method. In this research, a number of 363 people answered the survey. There was a significant difference in the categories of occupation, education and age regarding confidence, doubt and view towards NIP. Research findings found that occupation, education and age were seemed to justify the decision made by the respondents either to accept or decline the vaccination at national level. Overall, the aspects of occupation, education and age should receive attention in the future in public health program implementation so that these categories can obtain much clearer information.